Fragmentation studies of Hydrogenated-Pyrene Polycyclic Aromatic Hydrocarbons in collisions with He. (July 2015) - de Ruette, N; Gatchell, M; Stockett, M H; Giacomozzi, L; Chen, T; Anderson, E K; Nascimento, R F; Wolf, M; Alexander, J D; Delaunay, R; Vizcaino, V; Rousseau, P; et al.
Synopsis: We have studied the fragmentation of Pyrene or hydrogenated Pyrene cations (C16 H + 10+ x with x = 0, 5, 6 and 16) in collision with He. We find that the carbon backbone fragmentation cross section increases with the number of H atoms added. This suggests that hydrogenation does not protect PAHs in, e.g., harsh interstellar environments.